Exploring Egyptian EFL Teachers’ Perceptions of Teacher Leadership - Salama, Amira (AUC Knowledge Fountain, 2018)
The current study is an attempt to understand how the Egyptian English as-a-foreign-language (EFL) teachers perceive the concept of teacher leadership, a topic that has not received considerable attention in the educational leadership literature in this context. Teacher leadership is regarded as an important practice for school reform. In Egypt, language teachers struggle to find their own voices and meet the challenges of the job inside and outside the classroom. Attempts at school and education reform often disregard teachers’ understanding and application of new policies. This may result in the failure of these attempts since teachers are well-versed in school complexities and have the tools to implement change on the ground. These challenging realities of teaching make it imperative to investigate how EFL teachers perceive the concept of teacher leadership, examine what factors may influence these perceptions and provide suggestions to foster teacher leadership in schools. Adopting the teacher leadership definition of Katzenmeyer and Moller (2009), this study used a questionnaire and interviews to collect data on teacher leadership perceptions. The results of the study showed that Egyptian EFL teachers perceive teacher leadership mainly in terms of excellent teaching and effective interaction among themselves. Some differences in perceptions were found to be linked to teachers’ years of experience, their involvement in professional development activities, their geographical locations and gender. School administrators’ support was also found to be important in influencing how teachers practice leadership in their schools. In light of the study results, it appears that professional teacher associations and education stakeholders need to provide support to teachers to guide them towards a more comprehensive understanding of leadership and encourage them to demonstrate their leadership skills in schools for education reform to be effective. EFL classroom teachers as well need to be more proactive in preparing themselves for a leading role outside the classroom. Teachers should seek professional development and persistently work for creating opportunities to build their professional communities beyond the walls of the classroom. Teacher leadership is, as emphasized in the current study, a result of the collective efforts of everyone involved.